Feasibility and Initial Performance of Simultaneous SPECT-CT Imaging Using a Commercial Multi-Modality Preclinical Imaging System. (3rd June 2015) - Osborne, Dustin R.; Austin, Derek W.
Abstract : Multi-modality imaging provides coregistered PET-CT and SPECT-CT images; however such multi-modality workflows usually consist of sequential scans from the individual imaging components for each modality. This typical workflow may result in long scan times limiting throughput of the imaging system. Conversely, acquiring multi-modality data simultaneously may improve correlation and registration of images, improve temporal alignment of the acquired data, increase imaging throughput, and benefit the scanned subject by minimizing time under anesthetic. In this work, we demonstrate the feasibility and procedure for modifying a commercially available preclinical SPECT-CT platform to enable simultaneous SPECT-CT acquisition. We also evaluate the performance of simultaneous SPECT-CT tomographic imaging with this modified system. Performance was accessed using a 57 Co source and image quality was evaluated withTc 99m phantoms in a series of simultaneous SPECT-CT scans.